Legal Protection Carried Out by the Financial Service Authority in a Dispute between Consumers and Insurance Companies in Indonesia - Pujiyono; Ahmad, Sufmi Dasco (International Journal of Social and Administrative Sciences, 2018)
This study aims to find out how the form of legal protection carried out by the Financial Service Authority towards consumers who experience disputes with insurance companies in Indonesia. This research is a normative legal research that is the prescriptive approach. The data are taken from secondary data types that consist of primary and secondary legal materials. Data collection techniques used are library studies, and the analytical techniques used are deductive by syllogism method. The result of the study shows that a form of repressive protections is carried out by the Financial Service Authority after a dispute between consumers and insurance services and a legal defense that contains many weaknesses. Settlement of disputes between consumers and Insurance Companies can be done through litigation/ court and non-litigation/ out of court settlement. In the litigation process through the Commercial Court. The non-litigation process that will carried out with the institution/ internal dispute resolution step, limited facilities through mediation that facilitated by Financial Services Authority and finally through the external dispute resolution or the arbitration institution.